Multifunctionality of silver closo-boranes - Mark Paskevicius (Nature Portfolio, 2017)
Silver compounds have long been known to possess exceptional solid-state conductivity. Here the authors present silvercloso-boranes in which facile Ag+migration occurs, leading to exceptionally high ion conductivities and potential utility in silver nanowire production and photocatalysis due to their semiconductivity.